Mertk Interacts with Tim-4 to Enhance Tim-4-Mediated Efferocytosis - Byeongjin Moon; Juyeon Lee; Sang-Ah Lee; Chanhyuk Min; Hyunji Moon; Deokhwan Kim; Susumin Yang; Heera Moon; Jaeseon Jeon; Young-Eun Joo; Daeho Park (Cells, 2020)
Apoptotic cells expressing phosphatidylserine (PS) on their cell surface are directly or indirectly recognized by phagocytes through PS-binding proteins. The PS-binding protein Tim-4 secures apoptotic cells to phagocytes to facilitate the engulfment of apoptotic cells. However, the molecular mechanism by which Tim-4 transduces signals to phagocytes during Tim-4-mediated efferocytosis is incompletely understood. Here, we report that Tim-4 collaborates with Mertk during efferocytosis through a biochemical interaction with Mertk. Proximal localization between the two proteins in phagocytes was observed by immunofluorescence and proximal ligation assays. Physical association between Tim-4 and Mertk, which was mediated by an interaction between the IgV domain of Tim-4 and the fibronectin type-III domain of Mertk, was also detected with immunoprecipitation. Furthermore, the effect of Mertk on Tim-4-mediated efferocytosis was abolished by GST-MertkFnIII, a soluble form of the fibronectin type-III domain of Mertk that disrupts the interaction between Tim-4 and Mertk. Taken together, the results from our study suggest that a physical interaction between Tim-4 and Mertk is necessary for Mertk to enhance efferocytosis mediated by Tim-4.